“The Ecstasy of the Between-Us”: Sharing the World in Michèle Roberts’s Relational Poetics - Szuba, Monika (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2022)
In Through Vegetal Being, Luce Irigaray writes about the importance of “cultivating and sharing life between all” as it will result in “the blossoming of all beings.” This perspective seems to reside at the centre of Michèle Roberts’s writing. Entangled in the natural world, her characters demonstrate an awareness of the necessity of grounding. Mud, this mixture of water and soil, is a recurrent motif, and a powerful symbol of remaining close to the earth. It also exemplifies the collapse of binaries frequently occurring in Roberts’s texts, including the intertwining of human and nonhuman beings particularly present in her poetry. Offering a weave of the spiritual and the worldly, Roberts frequently foregrounds our corporeal existence, which constitutes a major theme in her work. Sensual and fleshly, her texts remain “in the tangle of brambles” (The Heretic’s Feast 6), immersed in the shivering, shifting, changing world, with all its intensities and sensations. This essay explores the significance of the vegetal and animal in the constitution of individual identity in Michèle Roberts’s poetic work. The analysis will focus on the relation of the self with the world, established in the spirit of cultivating and sharing.